MODERN DIGITAL DISTANCE LEARNING TECHNOLOGIES: CHALLENGES OF FUTURE TEACHER TRAINING - Budnyk, Olena; Zozuliak-Sluchyk Rоksoliana; Nedilskyi, Stepan; Chervinska, Inna; Malanіuk Taras; Prevysokova, Nataliia; Ketsyk-Zinchenko, Uliana (Revista Inclusiones, 2020)
The article deals with the problem of using digital distance learning technologies, intensified in the current situation because of the coronavirus pandemic.Today’s societal challenges require teachers with innovative thinking, the ability to adapt to different professional conditions, the ability to respond to innovations and use them in digital communication with students online.There is a necessity to train future teachers to use digital technologies and tools in the educational process. The article presents the results of an empirical study of this problem.The survey method revealed the state of the outlined problem in educational practice, secondary school teachers’ and university educators’ understanding of problems and challenges regarding the usage of digital resources and distance learning tools.The sample included different age categories of respondents: Boomer Generation, Generation X and Millenials (Generation Y). It was found that respondents have difficulties in using didactic knowledge in distance learning (36.4%),creation of moral and psychological comfort (36.4%), organization and stimulation of activity (25.5%) and effective online communication (21.8%).It wasrevealed that in the conditions of the pandemic a significant part of practitioner-teachers (53.8%) faced the problem of insufficient technical support of the educational institution;17.3% of respondents are dissatisfied with the level of their digital literacy and are looking for ways to increase professional competence in this area. The authors of the article proposedigital tools and applications for distance learning, as well as outline ways to prepare teachers for the effective use of digital learning technologies. Organizational forms of distance learning are presented, such as: online courses, online counseling, hackathons, webinars, online trainings, interactive educational platforms, virtual / remote laboratories, as well as visits to international science museums and virtual technology parks, creation of communication platforms taking into account scientific interests, etc.